Mobile App Usability, Data Privacy, Brand Loyalty, and Customer Retention in Indonesia's Online Transportation Services Industry - Bahar, Anisa; Prananta, Arie Wahyu; Afifudin, Moch; Taufikur Rahman, Rahmat (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the relationship between mobile app usability, data privacy, brand loyalty, and customer retention in Indonesia's online transportation services industry. Using partial least squares structural equation modeling (PLS-SEM) to analyze data from a sample of users, the results show that both mobile app usability and data privacy significantly affect brand loyalty, which, in turn, strongly predicts customer retention. Additionally, usability and privacy have direct effects on retention. The mediation analysis highlights the role of brand loyalty in amplifying the impact of usability and privacy on retention. These findings offer practical insights for online transportation service providers seeking to improve customer experiences, loyalty, and retention.